Measuring and exploring the structure of teachers' educational beliefs. (September 2021) - Valckx, Jasja; Vanderlinde, Ruben; Devos, Geert
Highlights: This study reports on developing teachers' subject-specific language beliefs scales. The developed scales have a reasonable fit and can be used in future research. Teachers agree with both teacher- and student-regulation of learning processes. This study found two beliefs structures: a constructivist and a traditional one. This study found two clusters of teachers that correspond to the beliefs structures. Abstract: This study explores the structure of French teachers' educational beliefs. First, instruments to measure these beliefs are adapted and developed. Data is collected through focus group discussions and an online survey ( n = 302). Factor analyses reveal a three-factor structure to measure teachers' general beliefs about teaching and learning: 'beliefs about student regulation of learning processes and knowledge construction', 'beliefs about teacher regulation of learning processes', and 'beliefs about knowledge reproduction'. Furthermore, a two-factor structure to measure teachers' subject-specific beliefs about French language teaching is found: 'traditional beliefs about French language teaching' and 'constructivist beliefs about French language teaching'. Second, this study explores the relationships between and within teachers' general beliefs about teaching and learning and their subject-specific beliefs about French language teaching. Results show two distinct and independent belief structures: a traditional and a constructivist belief structure. Via cluster analyses, two clusters of teachers are found whose beliefs are consistent with these belief structures.